Nation-building in a plural society towards bangsa Malaysia - Norizan Abd Majid; Sity Daud (Penerbit Universiti Kebangsaan Malaysia, 2021)
The book examines the role of nation-building in plural society and its viability to redress the huge challenges of nation formation.